Modern Methods of The Treatment of Phia Hernia - Kurbaniyazov Zafar Babazhanovich; Davlatov Salim Sulaimanovich; Usarov Sherali Nasritdinovich; Abdurakhmanov Diyor Shukurillaevich (Periodica Journal, 2022)
The experience of treating 61 patients with inguinal hernias, who underwent 69 alloplastic hernioplasties, was analyzed. The Lichtenstein method of alloplasty with polypropylene meshes was mainly used. Good immediate and long-term results have been obtained. No relapses were observed during the three years of follow-up. Alloplasty should be more widely used for the treatment of inguinal hernias.
Keywords: inguinal hernia; polypropylene meshes; alloplasty according to the Liechtenstein method; during